Enseigner la culture de l’autre : la tentation culturaliste - Regis Machart; Sin Zi Chin (Multilinguales)
The Didactics of culture and interculturality often follows a solid approach, ignoring the fundamental diversity of each culture. Lecturers are confronted with a dilemma : How to teach the ‘culture’ of the Other without falling into the trap of stereotyping ? This contribution analyzes the discourse of French lecturers in Malaysia, a multicultural and multilingual country, and questions their theoretical framework of culture. It appears that more teaching material which takes into account agreater sense of diversity is needed for the classroom.